2019
DOI: 10.1038/s41598-019-45476-6
|View full text |Cite
|
Sign up to set email alerts
|

Topology Effects on Sparse Control of Complex Networks with Laplacian Dynamics

Abstract: Ease of control of complex networks has been assessed extensively in terms of structural controllability and observability, and minimum control energy criteria. Here we adopt a sparsity-promoting feedback control framework for undirected networks with Laplacian dynamics and distinct topological features. The control objective considered is to minimize the effect of disturbance signals, magnitude of control signals and cost of feedback channels. We show that depending on the cost of feedback channels, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Beyond mathematical modeling, systems theory has been particularly useful to understand and characterize various biological systems [4]. Graph-theoretic tools have also found applications in analyzing and understanding biological networks as functional modules [5][6][7][8][9]. Notably, it has been seen through experiments [10] that the design principles, for any given biological response, are relatively conserved across organisms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond mathematical modeling, systems theory has been particularly useful to understand and characterize various biological systems [4]. Graph-theoretic tools have also found applications in analyzing and understanding biological networks as functional modules [5][6][7][8][9]. Notably, it has been seen through experiments [10] that the design principles, for any given biological response, are relatively conserved across organisms [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that some diffusion processes present not trivial behaviors such as super-diffusion, by which the multiplex structure reaches a steady-state faster than any of the layers in isolation [35]. This approach has been successfully used in several applications [36][37][38][39][40] and later expanded to other phenomena [41] such as synchronization and reaction-diffusion processes [42][43][44][45]. Diffusion times computed by diffusion capacity are in excellent agreement with those determined by the Laplacian matrix's smallest positive eigenvalue (see section B of the SI).…”
Section: Diffusion Capacitymentioning
confidence: 94%
“…• In Constantino et al, 129 a large amount of random networks with diverse topological features were examined, and it was shown that modularity and centrality (or hierarchy), i.e., the existence of communities and the existence of a small core of nodes to which all nodes are inclined to connect, are the main topological features to lower the aforementioned total control cost when the weight of controller sparsity is moderate and high, respectively.…”
Section: Inspirations From Network Structures In Biologymentioning
confidence: 99%